2021
DOI: 10.2991/assehr.k.211021.002
|View full text |Cite
|
Sign up to set email alerts
|

EFL Students’ Problems in Writing Argumentative Essays

Abstract: Writing in a foreign language is not easy because students have to consider not only the content but also the vocabulary, grammar, and mechanics. This study aimed to investigate the problems that English students have in writing argumentative essays. The subjects of this research were 55 students who were enrolled in Advanced Writing course at English Language Education Study Program of FKIP Universitas Lambung Mangkurat. A descriptive design within mixed method approaches was applied. A questionnaire was dist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 11 publications
0
0
0
Order By: Relevance
“…Similar research was carried out by Ka Kan Dee (2017) on 60 law students in Thailand, and grammar turned out to be difficult for them. In line with these studies, Indonesian university students encountered grammar issues regarding formatting words, word classes, and errors in using words and articles (Fajaryani et al, 2021;Rahmatunisa, 2014;Saputra et al, 2021). The research findings reported by Dang et al (2020), who distributed questionnaires to 90 Vietnamese English major sophomore students at Tay Do University and interviewed some of them, indicated that grammar was one of the difficulties encountered by these students.…”
Section: Grammarmentioning
confidence: 88%
See 3 more Smart Citations
“…Similar research was carried out by Ka Kan Dee (2017) on 60 law students in Thailand, and grammar turned out to be difficult for them. In line with these studies, Indonesian university students encountered grammar issues regarding formatting words, word classes, and errors in using words and articles (Fajaryani et al, 2021;Rahmatunisa, 2014;Saputra et al, 2021). The research findings reported by Dang et al (2020), who distributed questionnaires to 90 Vietnamese English major sophomore students at Tay Do University and interviewed some of them, indicated that grammar was one of the difficulties encountered by these students.…”
Section: Grammarmentioning
confidence: 88%
“…These results are in agreement with the findings from the previous studies. There have been several previous studies (e.g., Beniche et al, 2021;Dang et al, 2020;Ka kan dee, 2017;Peloghitis, 2016;Saputra et al, 2021) that reported the students' vocabulary difficulties in general. In particular, (Ka kan dee, 2017) analyzed 60 Law Thai students' essays interviewed them, and confirmed that the students had an insufficient academic vocabulary.…”
Section: Vocabulary Is Difficult I Have Only Some Familiar General Wo...mentioning
confidence: 99%
See 2 more Smart Citations
“…Writing an argumentative essay is a double burden for EFL students whose first language is not English (Hyland, 2013). Many students in different EFL contexts experience difficulties in constructing argumentative essays, for instance, in China (Liu & Stapleton, 2014;Bychkovska & Lee, 2017), in Indonesia (Saputra et al, 2021;Tasya, 2022), in Iran (Ghanbari & Salari, 2022), in Japan (Peloghitis, 2017), in Myanmar (MayOo & Eto, 2023) and in Thailand (Ka-kan-dee & Kaur, 2015). EFL learners are frequently described as having limited capacity to write well-organized arguments with clear and relevant evidence and demonstrate their opinions about a given topic or issue along with the opposing views.…”
mentioning
confidence: 99%